Automated Testing to Evaluate Employee Attendance System Performance Using Gtmetrix - Hafizhah, Nurul; Hidayat, Ahmad Tri (Compiler, 2024)
The employee attendance system is an important component in human resource management that functions to efficiently record and monitor employee attendance. With the increasing reliance on information technology, it is essential to ensure optimal performance and a satisfying user experience. It is important for companies to ensure that this system functions well and responsively. This study aims to evaluate the performance of an employee attendance system through automated testing using the website performance analysis tool GTMetrix. By adopting automated testing using GTMetrix on this system to measure and analyze its performance, this research also offers an objective and efficient approach to identifying performance bottlenecks. The results of this research can serve as a reference for information system developers in designing and implementing a more optimal employee attendance system. In addition, the research also provides insights into the importance of optimizing website performance in the context of business applications. The results of the performance and structure testing analysis on this system using GTMetrix achieved an A grade with a performance score of 100% and a structure score of 100%. This research emphasizes the importance of automated testing as a tool to enhance and improve the performance of information systems, thereby meeting user needs and supporting more effective human resource management.